Graphene nanoplatelets/barium titanate polymer nanocomposite fibril: a remanufactured multifunctional material with unprecedented electrical, thermomechanical, and electromagnetic properties - Mishra, Raghvendra Kumar; Goel, Saurav; Chianella, Iva; Yazdani Nezhad, Hamed (Wiley, 2023)
A novel, zero-waste and recycling plastic waste solution is introduced, to scalably produce graphene nanoplatelets/barium titanate (GNP/BaTiO3) polymer nanocomposite fibrils. A comprehensive investigation is performed to evaluate the compatible and non-compatible recycled polypropylene (PP)/polyethyleneterephthalate (PET) blends combined with functional (electrical, piezoelectric,and dielectric) materials for in-situ fibril production. The nanocompositefibrils made from recycled PP, PET and GNPs/BaTiO3 with high-aspect ratio disparity (400:1) are produced, which exhibit significantly enhanced electrical, thermomechanical, and electromagnetic characteristics. Single-screw extrusion is utilised to fabricate the fibrils with the in-situ fibril morphology of PET and GNPs/BaTiO3 leading to improved electrical conductivity. It is demonstrated that such fibril morphology restricts the chain mobility of polymer molecules, and ultimately increases viscosity and strain energy. Moreover, the study demonstrates a positive reinforcement effect from the utilisation of PET fibrils and GNPs/BaTiO3 in a PP matrix, dominated by the high-aspect ratio, stiffness, and thermal stability of GNPs/BaTiO3. Furthermore, it is observed that the mechanical properties and tension-bearing capacity of the PP are significantly improved by such incorporation. The study also demonstrates that the protection of the remanufactured nanocomposites against electromagnetic interference is significantly improved with the increasing GNPs/BaTiO3 content and the morphological transition from spherical to fibril-shaped PET.
Keywords: barium titanate; electromagnetic interference shielding; graphene nanoplatelets; multifunctional composites; nanocomposite fibrils; thermal stability